Pemanfaatan Bahan Rujukan Sebagai Referensi Mahasiswa Semester Akhir Di Perpustakaan Universitas Labuhan Batu ( ULB ) - Juni Ervina Sari; Yusra Dewi Siregar; Yusniah Yusniah (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
The aim of this research is to find out the reference materials that students use in completing their final assignments. To find out the use of reference materials in the Labuhan Batu University library. To find out the obstacles for final semester students in servicing reference materials at the Labuhan Batu University library. In this research, the author used a type of field research (Field Research), with a qualitative descriptive method, and used data collection techniques through interviews, documentation and observation. The informants in this research were users at the Labuhanbatu University library who were selected by researchers according to the research subject criteria. The results of this research show the use of reference materials in the Labuhan Batu University library to find them quickly and precisely, more broadly to explore various information needed by final semester students. Many use the library to look for information or references they need as reference materials or references in the form of books. texts and special references for scientific works such as theses, journals, articles as final semester student references in the Labuhan Batu University library.